2016
DOI: 10.1159/000445871
|View full text |Cite
|
Sign up to set email alerts
|

Human Basic Fibroblast Growth Factor Inhibits Tau Phosphorylation via the PI3K/Akt-GSK3β Signaling Pathway in a 6-Hydroxydopamine-Induced Model of Parkinson's Disease

Abstract: Background: Basic fibroblast growth factor (bFGF) has been increasingly investigated due to its neuroprotection in neurodegenerative disorders. Because there are still no cures for any of these disorders, it is crucial to identify new therapeutic targets and screen potential drugs. The increased phosphorylation of tau at Ser396 leads to intracellular tau accumulation, which forms neurofibrillary tangles in Parkinson's disease (PD). In this study, neuroprotection by bFGF was observed, and the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
(82 reference statements)
0
12
0
1
Order By: Relevance
“…PG itself, administered intranasally, has been used as a therapy by the Voelker group to effectively inhibit respiratory syncytial virus infection (Numata et al, 2010; Numata et al, 2013) and influenza A virus (Numata et al, 2012). Moreover, lipid based colloidal carriers are able to cross the blood brain barrier (BBB) when administered intranasally (Ganesan et al, 2018; Mittal et al, 2014; Patel and Patel, 2017; Tapeinos et al, 2017) and have recently been shown to be efficient drug delivery vehicles in the treatment of intrinsic brain tumors (van Woensel et al, 2013) and neurodegenerative diseases including Alzheimer’s (Agrawal et al, 2018; Tapeinos et al, 2017) and Parkinson’s (Tapeinos et al, 2017; Yang et al, 2016). Given the historical difficulties in treating the neurological effects of NPC disease, the development of a minimally invasive, effective treatment with intrinsic ability to cross the BBB is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…PG itself, administered intranasally, has been used as a therapy by the Voelker group to effectively inhibit respiratory syncytial virus infection (Numata et al, 2010; Numata et al, 2013) and influenza A virus (Numata et al, 2012). Moreover, lipid based colloidal carriers are able to cross the blood brain barrier (BBB) when administered intranasally (Ganesan et al, 2018; Mittal et al, 2014; Patel and Patel, 2017; Tapeinos et al, 2017) and have recently been shown to be efficient drug delivery vehicles in the treatment of intrinsic brain tumors (van Woensel et al, 2013) and neurodegenerative diseases including Alzheimer’s (Agrawal et al, 2018; Tapeinos et al, 2017) and Parkinson’s (Tapeinos et al, 2017; Yang et al, 2016). Given the historical difficulties in treating the neurological effects of NPC disease, the development of a minimally invasive, effective treatment with intrinsic ability to cross the BBB is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In the normal adult brain, CDK5 activated by protein p35 (or p39) phosphorylates Ser199 and Ser202, and GSK3β is able to phosphorylate only Ser202. If GSK3β is up-regulated, it recognizes the 202pSPGT205 site created e.g., by p35/CDK5, and efficiently phosphorylates Thr205 [105,106]. Additional phosphorylation at Ser208 was achieved in vitro by addition of the rat brain extract [103].…”
Section: Proline-rich Domainsmentioning
confidence: 99%
“…Our previous studies showed that intranasal administration of TAT-haFGF could improve cognition and reduce Aβ deposits more significantly in APP/PS1 mice compared with intravenous injection 18, 21, 22, 23. In an animal model of Parkinson’s disease induced by 6-OHDA, liposomes markedly assisted the delivery of basic fibroblast growth factor (bFGF) to the striatum and substantia nigra (SN), and they enhanced the neuroprotective effects of bFGF on dopaminergic neurons 46 . Liposomes also enhanced the levels of aFGF significantly in the EC, accompanied by amelioration in cognitive and non-cognitive behavioral deficits.…”
Section: Discussionmentioning
confidence: 99%